Studies of energy during strong and weak monsoon situations over India - PANDEY, SN; CHATTOPADHYAY , J; SINGH, US (MAUSAM, 1989)
The basic, forms of energy, namely, Az, AH, Kz and KE ,were computed for strong and weak monsoon. situations over India at different pressures by a five-level diagnostic model. The vertically integrated daily variation suggests that the Intensity of the monsoon is associated with the Intensity of eddy form of energy.